Vowel adaptations of Indonesian loanwords into dialects of Acehnese: Reinforcing Acehnese identity - Zulfadli A. Aziz; Rob Amery; Faisal Mustafa (Universitas Syiah Kuala, 2023)
Acehnese, like other regional languages throughout Indonesia, is in constant and intense contact with Bahasa Indonesia, a lingua franca of Indonesia. Not surprisingly, many Indonesian loanwords are flooding into Acehnese. There are some interesting sound changes affecting both consonants and vowels, phonotactics, and stress. This paper explores the vowel changes occurring in Indonesian loanwords when used within dialects of Acehnese. A list of 285 well-established loanwords was compiled and recorded from native speakers of each of the four main Acehnese dialects (North Aceh, Pidie, Greater Aceh, and West Aceh). The informants were lecturers or postgraduate students and fluent bilingual speakers of both a selected Acehnese dialect and Indonesian. Phonemic transcriptions were compared with their Indonesian correspondences. The results of this study show that the behaviour of the vowels in this list of Indonesian loanwords is not a simple case of phonological assimilation, as usually occurs in loanword phonology, but rather often exhibits phonological dissimilation and must be an expression of Acehnese identity. In particular, the high back unrounded vowel /ɯ/ is a salient Acehnese vowel not found in Indonesian. A wide range of Indonesian vowels is frequently replaced by this vowel, resulting in the loanwords sounding distinctively Acehnese. The conditions when such changes occur are discussed in the paper.